Effect of Na + Substitution on the Phase, Microstructure, Electrical and Energy Storage Properties of BSBZNT Ceramics Prepared by the Solid-State Combustion Technique - Wistsarut Chongsatan; Ratirom Didpim; Phongthorn Julphunthong; Bhoowadol Thatawong; Naratip Vittayakorn; Theerachai Bongkarn (Integrated ferroelectrics, 2023)
Abstract(Ba0.704Sr0.176Bi0.12)1-xZn0.08Nb0.04Ti0.88O3-Nax (BSBZNT-xNa) ceramics with x = 0, 0.01, 0.03 and 0.05 mol%, were prepared by the solid-state combustion technique. The samples were calcined and sintered at 950 °C and 1375 °C, respectively, for 2 h. The phase, microstructure, dielectric, ferroelectric and energy storage properties were investigated. The X-ray diffraction patterns of the BSBZNT-xNa powders showed a perovskite phase for all samples. When x increased from 0-0.03, the average particle size increased from 380 to 480 nm, then decreased to 420 nm. All sintered samples showed the coexistence of the orthorhombic and cubic phases. The average grain size was in the range of 2.03 to 1.39 µm. The BSBZNT-0.01Na ceramic exhibited the highest dielectric properties at room temperature (ɛr = 902, tanδ = 0.10), the lowest remanent polarization (Pr = 0.10 µC/cm2), coercive field (Ec = 0.43 kV/cm), and the highest energy storage efficiency (η ∼ 94.70%) measured under an electric field of 70 kV/cm.Keywords: BSBZNT-xNa ceramicsolid-state combustionphase structuremicrostructureenergy storage AcknowledgmentsThe authors wish thank the Department of Physics, Facullty of Science, Nareasuan University for provision of supporting facilities. Thanks are also given to Dr.Kyle V.Lopin for his help in editing the menuscript.Disclosure StatementNo potential conflict of interest was reported by the author(s).Additional informationFundingThis work was supported by Naresuan University (NU) and National Science, Research and Innovation Fund (NSRF) with Grant No. R2566B067. The work of Naratip Vittayakorn were supported by KMITL under the Grant number KREF116501.
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Acoustic Wave Resonator Technologies